2007
DOI: 10.1007/s00426-007-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of problem size, operation, and working-memory span on simple-arithmetic strategies: differences between children and adults?

Abstract: Adult's simple-arithmetic strategy use depends on problem-related characteristics, such as problem size and operation, and on individual-diVerence variables, such as working-memory span. The current study investigates (a) whether the eVects of problem size, operation, and working-memory span on children's simple-arithmetic strategy use are equal to those observed in adults, and (b) how these eVects emerge and change across age. To this end, simple-arithmetic performance measures and a working-memory span measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 59 publications
5
86
0
1
Order By: Relevance
“…The test revealed significant differences between the mean time of the place-value strategy (p=0.01) and the aspresented (p=0.13) and other (p=0.58) strategies. This agrees with Imbo and Vandierendonck (2008) who argued that computational strategies are more efficient than procedural strategies. Therefore the MuTAT application can detect the relative efficiency of strategies…”
Section: Strategy Efficiencysupporting
confidence: 90%
See 2 more Smart Citations
“…The test revealed significant differences between the mean time of the place-value strategy (p=0.01) and the aspresented (p=0.13) and other (p=0.58) strategies. This agrees with Imbo and Vandierendonck (2008) who argued that computational strategies are more efficient than procedural strategies. Therefore the MuTAT application can detect the relative efficiency of strategies…”
Section: Strategy Efficiencysupporting
confidence: 90%
“…Overall, the literature suggests that conceptual understanding plays an important role in strategy adoption and generation. Imbo (2008) described three classes of strategies that can be used to solve mental arithmetic problems. These are; direct memory retrieval, procedural strategies such as counting (e.g., 8+5=9...10...11...12...13; 9 x 6 = 9...18...27...36...45...54) and transformational strategies (e.g., 8 + 5 = 8 + 2 + 3; 9 x 6 = 10 x 6 -6).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…This model has received strong support from several studies (Barrouillet & Fayol, 1998;Campbell & Timm, 2000;Geary & Brown, 1991;Geary & Burlingham-Dubree, 1989;Hamann & Ashcraft, 1986;Imbo & Vandierendonck, 2007;Imbo & Vandierendonck, 2008;Reder, 1988) and has provided a theoretical basis to the recurrent observation that adults retrieve from memory the answer of small additions instead of having to calculate it (Ashcraft, 1982;Ashcraft, 1987;Ashcraft & Battaglia, 1978;Ashcraft & Stazyk, 1981;Barrouillet & Fayol, 1998;Campbell, 1987a;Campbell, 1987b;LeFevre, Sadesky, & Bisanz, 1996;Miller, Perlmutter, & Keating, 1984). Thus, it is almost universally admitted that small additions have so often been encountered that their answer is necessarily retrieved from memory in adults (see Zbrodoff & Logan, 2005, for a review).…”
Section: Introductionmentioning
confidence: 96%
“…While only a few studies have examined the effect of working memory on arithmetic strategy selection, it has been found that working memory does have an impact (Imbo & Vandierendonck, 2008a, 2008bHecht, 2002;Seyler, Kirk, & Ashcraft, 2003). For example, during arithmetic problem solving, higher working memory capacity participants used a retrieval strategy more often than low-span participants (Imbo & Vandierendonck, 2008b).…”
Section: Discussionmentioning
confidence: 99%